2022
DOI: 10.1021/acs.jproteome.2c00174
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Cleavable Biotin Tags for Peptide-Centric Chemoproteomics

Abstract: Click chemistryspecifically the copper-catalyzed azide-alkyne cycloadditionhas enabled the development of a wide range of chemical probes to analyze subsets of the functional proteome. The "clickable" proteome can be selectively enriched by using diverse cleavable biotin tags, but the direct identification of probe/tag-modified peptides (or peptide-centric analysis) remains challenging. Here, we evaluated the performance of five commercially available cleavable biotin tags in three most common chemoproteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 48 publications
(72 reference statements)
1
36
0
Order By: Relevance
“…We prioritized studies that reported high coverage datasets that measured one or more of the following parameters: (1) total number of cysteines identifiable by the pan-cysteine reactive probes, (2) measurement of cysteine intrinsic reactivity towards iodoacetamide alkyne (IAA, 1) and (3) assaying cysteine ligandability (Figure 1A). We collected a total of nine datasets that fulfilled our criteria (Figure 1B for all datasets used) 2,[4][5][6][7][8][9][10][11] .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We prioritized studies that reported high coverage datasets that measured one or more of the following parameters: (1) total number of cysteines identifiable by the pan-cysteine reactive probes, (2) measurement of cysteine intrinsic reactivity towards iodoacetamide alkyne (IAA, 1) and (3) assaying cysteine ligandability (Figure 1A). We collected a total of nine datasets that fulfilled our criteria (Figure 1B for all datasets used) 2,[4][5][6][7][8][9][10][11] .…”
Section: Resultsmentioning
confidence: 99%
“…Cysteine proteomics experiments can be generally classified into four main categories: (1) identification, (2) measuring hyperreactivity, (3) measuring ligandability and (4) measuring redox state. (1) We consider identification studies as those aiming to increase coverage of cysteine containing peptides using label free quantification [4][5][6] . (2) Hyperreactivity experiments measure the intrinsic reactivity of cysteines towards highly electrophilic probes [7][8][9][10] , while (3) ligandability experiments measure the intrinsic ligandability or potential 'druggability' of cysteines using libraries of drug-like electrophilic molecules, natural products, and lipid derived electrophiles 2,11,[15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations